Lean manufacturing practices and integration of IR 4.0 technologies for sustainability in the healthcare manufacturing industry / Muslim Diekola Akanmu ... [et.al.] - Akanmu, Muslim Diekola; Nordin, Norshahrizan; Gunasilan, Uma (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Providing affordable, safe, and reliable care while improving performance and efficiency remains a challenge in the healthcare sector. This study reviews the previous researches on the effect of lean manufacturing practice (LMP) and industrial revolution 4.0 technologies (IR 4.0 tech) on sustainability; however, there is still a paucity of literature on the implementation of the practices in the healthcare sector. Although studies have shown that LMP has significantly impacted organizational performance in the manufacturing industry, the integrated effects of LMP and IR 4.0 technologies on sustainable performance have not been empirically examined in the healthcare sector. This study, therefore, intends to have a preliminary conceptual approach to the joint effect of LPM and IR 4.0 technologies on sustainability before subsequently going for an empirical study to address the gap in the sector. The study aimed to confirm the future direction of the public health sector that has recently been employing new technologies in its service systems. The consequent study shall be based on data collected from the health practitioners who are working and familiar with the smart tools to expedite services for healthcare. However, this present study unfolds the significant contribution of operations management practices and how sustainable performance can be enhanced through performance variation and strategic implementation in the healthcare sector. Lean practices and IR 4.0 technologies lead to improvement and operational sustainability when fully implemented in the healthcare sector.